Understanding suicidal pathways through the lens of a Dual-System Model of Suicidality in real-time: The potential of ecological momentary assessments - Brüdern, Juliane; Glaesmer, Heide; Berger, Thomas; Spangenberg, Lena (Frontiers in Psychiatry, 2022)
Within the ideation-to-action framework, existing theories of suicidal thoughts and behaviors (STBs) primarily focus on the linear progression of suicide risk. This however neglects growing evidence that many suicidal individuals do not experience their suicide attempt as a planned action, and in some instances deny even having experienced any suicidal thoughts. Furthermore, recent research has found that risk factors differ substantially between persons and that this is reflected in the variety of suicidal pathways. Considering the strong variability of STBs, new innovative theoretical concepts and assessment methods are needed to advance our understanding of multiple suicidal pathways. In this review, we apply a dual-system framework to suicidality, the Dual-System Model of Suicidality (DSMS), which accounts for two different systems of information processing and behavior. The first of these described is the reflective system, whereby STBs are viewed from a self-regulation perspective and thusly considered as maladaptive coping behavior to perceived discrepancies regarding important goals. Applying a feedback-based view such as this to STBs provides a deeper understanding into underlying psychological processes involved in the development of STBs. The second system described by the DSMS is the impulsive system. Here, STBs are seen as a maladaptive self-organizing pattern that gets activated in high-risk situations of acute stress, negative affect, and when resources of the reflective system are depleted. In this context, the DSMS is informed by a strength model of self-regulation, which assumes that self-regulation resources are limited, an aspect with important theoretical and clinical implications for the development of STBs. In order to demonstrate the theoretical and practical utility of the DSMS, this review draws mainly on studies using ecological momentary assessment (EMA), a technology that allows to investigate moment-to-moment changes in STBs, and is therefore well suited for capturing the complex interplay of self-regulatory and impulsive processes proposed by the DSMS. The application of a dual-system framework to suicide research represents an innovative and integrative approach for expanding our knowledge about fundamental processes and how their dynamics lead to STBs. The usefulness of the DSMS, implications for future suicide research with EMA, and clinical implications are discussed.